Stabilization of Immobilized Lipases by Intense Intramolecular Cross-Linking of Their Surfaces by Using Aldehyde-Dextran Polymers - Alejandro Orrego; Rohollah Ghobadi; Sonia Moreno-Perez; Adriana Mendoza; Gloria Fernandez-Lorente; Jose Guisan; Javier Rocha-Martin (International Journal of Molecular Sciences, 2018)
Immobilized enzymes have a very large region that is not in contact with the support surface and this region could be the target of new stabilization strategies. The chemical amination of these regions plus further cross-linking with aldehyde-dextran polymers is proposed here as a strategy to increase the stability of immobilized enzymes. Aldehyde-dextran is not able to react with single amino groups but it reacts very rapidly with polyaminated surfaces. Three lipases—from Thermomyces lanuginosus (TLL), Rhizomucor miehiei (RML), and Candida antarctica B (CALB)—were immobilized using interfacial adsorption on the hydrophobic octyl-Sepharose support, chemically aminated, and cross-linked. Catalytic activities remained higher than 70% with regard to unmodified conjugates. The increase in the amination degree of the lipases together with the increase in the density of aldehyde groups in the dextran-aldehyde polymer promoted a higher number of cross-links. The sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) analysis of those conjugates demonstrates the major role of the intramolecular cross-linking on the stabilization of the enzymes. The highest stabilization was achieved by the modified RML immobilized on octyl-Sepharose, which was 250-fold more stable than the unmodified conjugate. The TLL and the CALB were 40-fold and 4-fold more stable than the unmodified conjugate.